English E-Worksheets Based on Wizer.me for Elementary Students - Dayu Retno Puspita; Philien Sophia; Rizki Zuliani (MIMBAR PGSD Undiksha, 2025)
In 21st-century learning, technology integration plays a crucial role in supporting the development of learning tools such as student worksheets (LKPD), teaching materials, and interactive media to create innovative learning processes that align with the demands of the digital era. However, its implementation in practice remains suboptimal, as learning activities are often limited to conventional assignments without meaningful use of technology. This study aims to explore and develop interactive electronic worksheets supported by Wizer.me as a learning medium for English instruction among elementary school students. The research adopts a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The validation process involved media and material experts, as well as student responses through a series of trial phases. Data were collected using questionnaires and analyzed through both quantitative and qualitative descriptive methods. The results indicate that the developed product achieved a very high level of feasibility based on expert assessments and positive student feedback. Overall, the interactive electronic worksheet assisted by Wizer.me proved effective in enhancing student engagement, motivation, and interest in learning English. The findings of this study highlight the importance of utilizing educational technology to strengthen interactive learning experiences and improve the quality of language learning in elementary education.